(2011) Modularization of Korea's development experience : public investment management reform in Korea: efforts for enhancing efficiency and sustainability of public expenditure - Kim, Jay Hyung (KDI School of Public Policy and Management, 2012)
The financial crisis that hit Korea in the last half of 1997 had a devastating impact on the Korean economy, causing the worst recession during the postwar era. In order to address the fundamental causes of the crisis and to revitalize the economy, the Korean government took bold and decisive steps to initiate comprehensive structural reforms. The major focus of reform in the fiscal and public sectors has been to adopt more market-oriented forces and managerial strategies to increase efficiency and transparency. Efforts were made to instill a performance-oriented approach in the system, which implied management of public expenditure, based on the principle of value for money. The government adopted a series of integrated (ex-ante, intermediate, and ex-post) quality control efforts for the efficient management of its public investment program. A strong and effective project appraisal study, to oversee the project selection process of the line ministries, was established by the budget ministry. A formal review process was introduced to ensure that funds were continually subjected to monitoring and evaluation. In addition, budgeting for public investment was simplified by reducing the number of special accounts and government funds. The practices of project appraisal in the earlier stage, and total cost management in the intermediate, were found to be more efficient. There was common ground on the intentions and functions of a performance management between the budget ministry and the line ministries. The government introduced the Medium Term Expenditure Framework (MTEF), with a top-down budgeting process in 2004 for fiscal year 2005. The MTEF pointed out a need to enhance the capacity for planning and prioritizing public investment programs in the line ministries. It also emphasized the need to change the role of the Ministry of Strategy and Finance (MOSF) as well. This paper seeks to explain the institutional arrangement and reform efforts of the Korean government for developing and managing public investment programs in the last decade, and to find lessons learned to further improve value for money. Section 2 presents a long history and tradition of public investment management system in Korea, under the initiative of the Korean Finance Ministry. This section points to a long tradition of sound and sustainable public investment management within the bodies of government planning and finance ministries, before the crisis in 1997. However, Section 3 discusses major reasons why a number of failures were found in Korean public investment management (PIM) before the IMF crisis. Section 4 presents a new institutional framework for PIM, including a reform to introduce the MTEF, and recent new PIM initiatives. Section 5 examines the evolution and performance of Korean PIM reform. Special attention will be paid to explain how public investment projects are selected, prioritized, and managed in the budget process. New initiatives of total project cost management (TPCM), preliminary feasibility study (PFS), re-assessment study of feasibility (RSF), and re-assessment of demand forecast will be presented and analyzed. The section will also evaluate the performance of these initiatives. Section 6 addresses some of the newly-adopted Korean public private partnership (PPP) projects, substituting traditional government investment. Section 7 presents major driving forces for success in Korea PIM reform. Based on the lessons learned from the PIM reform, seven factors that facilitated successful reform will be highlighted. The last section provides a concluding remark with challenges ahead for a better PIM scheme in the future.
Keywords: Economic Policy; Public investments